Penerapan Pendidikan Agama Islam Pada Anak Usia Dini dalam Keluarga di Desa Sidorejo Kecamatan Belitang Jaya - Ihsanudin, Muhammad; Humairoh, wahidatul; Andi, Feri (Prodi Pendidikan Agama Islam, 2023)
Research paper: the family is the primary group in society whose role is very important in creating a healthy culture. Because it is from the family that good culture and good society begin. So it is not surprising that good culture and good society begin. So it is not surprising that the family is the first madsarah for children to receive a good education. This research raises the issue of implementing Islamic religious education for early childhood in families in Sidorejo village Belitang Jaya. This research uses a qualitative approach, namely understanding the phenomena experienced by the research subjects. The data collection techniques used were interviews, observation, and documentation. The result of this research can be concluded that the implementation of Islamic religious education for early childhood which has been optimally carried out by parents in the family in Sidorejo village Belitang Jaya district is the implementation of faith education, implementation of moral education, implementation of education.